2007
DOI: 10.1007/s00280-007-0498-4
|View full text |Cite
|
Sign up to set email alerts
|

A phase I and pharmacokinetic study of sunitinib administered daily for 2 weeks, followed by a 1-week off period

Abstract: The 2/1 schedule of sunitinib 50 mg was tolerable, and no significant drug accumulation was demonstrated. The safety profile on this schedule was consistent with the safety profile of sunitinib when administered on a 4-week on, 2-week off schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(76 citation statements)
references
References 18 publications
9
65
0
2
Order By: Relevance
“…In agreement with previous reports (Mendel et al, 2003), nanomolar concentrations (10-100 nM) of sunitinib inhibited VEGF-induced phosphorylation of VEGFR2 in human endothelial cells ( Figure 1a) and VEGF-induced endothelial cell proliferation (Figure 1b). These concentrations are clinically relevant, as circulating concentrations of sunitinib measured in patients are in the nanomolar range and do not typically exceed 200 nM (Faivre et al, 2006;Britten et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with previous reports (Mendel et al, 2003), nanomolar concentrations (10-100 nM) of sunitinib inhibited VEGF-induced phosphorylation of VEGFR2 in human endothelial cells ( Figure 1a) and VEGF-induced endothelial cell proliferation (Figure 1b). These concentrations are clinically relevant, as circulating concentrations of sunitinib measured in patients are in the nanomolar range and do not typically exceed 200 nM (Faivre et al, 2006;Britten et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Our clinical trial is, to the best of our knowledge, the first phase 2 clinical trial that has examined the effect of sunitinib solely on DTC, ensuring a homogeneous study population. Two phase 1 clinical trials reported a PR in two patients with thyroid cancer (one patient in each study) after treatment with sunitinib (21,22). Several groups have initiated phase 2 clinical trials of sunitinib in thyroid cancer.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…In phase I clinical trials the incidence of CTC grade >=3 hypertension was 7.3%. [57] In single-agent phase II clinical trials with sunitinib the rates of grade 1-2 and grade 3 hypertension were 8.4% and 7.5% respectively. [58] In phase III clinical trials which established the efficacy of sunitinib in gastrointestinal stroma tumors (GISTs) and renal cell carcinoma grade 3 hypertension was more frequent in the sunitinib group than in the placebo group (3% versus 0%) or the interferon group (8% versus 1%).…”
Section: Mechanism Of Cardiotoxicity Of Sunitinbmentioning
confidence: 99%
“…[59,60] In phase I clinical trials of sunitinib two of 55 patients developed left ventricular dysfunction and heart failure. [57] In the phase II clinical trials of sunitinib in renal cell carcinoma 8.9% of patients developed a reduction in LVEF. [58] Grade 3 reductions in LVEF were seen in a phase III trial of renal cell carcinoma.…”
Section: Mechanism Of Cardiotoxicity Of Sunitinbmentioning
confidence: 99%